2021
DOI: 10.1371/journal.pone.0251381
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic-specific reference range affects the efficacy of quadruple test as a universal screening for Down syndrome in a developing country

Abstract: Objective To evaluate the efficacy of the quadruple test for potential use as a Thai national policy for Down syndrome (DS) screening and establish an accurate equation for risk estimation of Down syndrome based on gestational age, weight and the ethnic-specific reference range of our population. Methods A prospective study was conducted on singleton pregnancies at 14 to 21 weeks of gestation to evaluate the efficacy of quadruple DS screening using the automatically calculated Western European descent factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 30 publications
(78 reference statements)
2
16
0
Order By: Relevance
“…A related study found that adding genetic sonogram screening in pregnancies identified as low risk for a Down syndrome fetus by cell-free DNA had a low positive predictive value [ 33 ]. To optimize the screening performance for Down syndrome, particularly in some developing countries in which maternal serum biomarkers are currently used but have lower detection rates than expected, such as in our setting [ 34 ], our study supports the idea of adding facial ultrasound markers in groups at moderate risk for Down syndrome to maternal serum biomarkers. As a previous study using only absent or hypoplastic nasal bone for Down syndrome screening reported a low detection rate for Down syndrome in Asian fetuses [ 35 ], adding multiple facial ultrasound markers should increase the detection rate of Down syndrome screening in our populations [ 36 ].…”
Section: Discussionsupporting
confidence: 71%
“…A related study found that adding genetic sonogram screening in pregnancies identified as low risk for a Down syndrome fetus by cell-free DNA had a low positive predictive value [ 33 ]. To optimize the screening performance for Down syndrome, particularly in some developing countries in which maternal serum biomarkers are currently used but have lower detection rates than expected, such as in our setting [ 34 ], our study supports the idea of adding facial ultrasound markers in groups at moderate risk for Down syndrome to maternal serum biomarkers. As a previous study using only absent or hypoplastic nasal bone for Down syndrome screening reported a low detection rate for Down syndrome in Asian fetuses [ 35 ], adding multiple facial ultrasound markers should increase the detection rate of Down syndrome screening in our populations [ 36 ].…”
Section: Discussionsupporting
confidence: 71%
“…AFP concentrations are usually greater as gestational age-progressed beyond the first trimester, but they dropped as maternal weight increases. 5 This supports the finding that maternal serum levels are affected by maternal weight-adjusted for Multiple of the Median (MoM). As a result, maternal weight adjustment for serum calculation also plays role.…”
Section: Introductionsupporting
confidence: 79%
“…Although many women with high maternal AFP do not have foetus abnormalities, there is a higher risk of obstetric problems such as premature rupture of membranes, placenta accreta, increta, and percreta. 5 According to the current studies, patients with a lower maternal body weight had higher serum AFP concentrations. AFP concentrations are usually greater as gestational age-progressed beyond the first trimester, but they dropped as maternal weight increases.…”
Section: Introductionmentioning
confidence: 51%
See 1 more Smart Citation
“…In the United Kingdom and the United States, it is routine for pregnant women to undergo serum screening for Down syndrome in the second trimester, either with A triple test (alpha-fetoprotein (AFP), human chorionic gonadotropin (HCG), and unconjugated estriol (UE)) or with A quadruple test (with the addition of statin A) [ 6 , 7 ]. Recently, early pregnancy screening using fetal neck translucency, HCG, and pregnancy-associated plasma protein A (PAPP-A) has supplied an earlier and more effective screening method [ 8 ].…”
Section: Introductionmentioning
confidence: 99%